Les ateliers collaboratifs, un outil de recueil collectif des représentations spatiales ? - Servane Gueben-Venière (EchoGéo)
Spatial representations are generally speaking collected in an individual way and only their analysis, which sounds complex, possibly leads to show social representations - shared by a social group - of space. However studying spatial representations coming from several groups of stakeholders who need to coordinate for instance in a crisis situation, requires to elaborate a new method to collect simultaneously and collectively these representations. This paper considers workshops as a tool to do so. These workshops have been experienced in June and July 2017 with stakeholders directly involved in the management of a major flood of the river la Seine, and show the contribution of geographic tools at the Metropolitan Paris scale.